Paracerceis sculpta (Crustacea: Isopoda: Sphaeromatidae), a Newly Introduced Species into Osaka Bay, Central Japan - Ariyama, H.; Otani, M. (Benthos Research, 2004)
Paracerceis sculpta (Holmes, 1904) [Crustacea: Isopoda: Sphaeromatidae] has been introduced into many localities in the world and its distribution has spread steadily. From July, 2000 to October, 2001, 809 individuals of this species were collected from an artificial sandy beach in Osaka Bay, central Japan. Descriptions of the morphological characters of both sexes are given based on the specimens. Comparison of these specimens with specimens previously identified as Paracerceis japonica Nunomura, 1988 collected in 1986 from Uwajima in Ehime Prefecture revealed synonymy of the two species, indicating that the occurrence in Osaka Bay is the second record of Paracerceis sculpta from Japan. The species was collected throughout most of the study period, and the abundance increased during the study period. Large males having elongate uropods, non-ovigerous females and juveniles were collected, with body lengths ranging from 1.3 mm to 10.3 mm. Paracerceis sculpta was probably introduced into Osaka Bay by ship-fouling in 1998, however, the donor area cannot be determined because ships arrive frequently in Osaka Bay from many ports around the world where P. sculpta occurs.